Does Social Media Strengthen the Effect of Narcissism, Envy, and Materialism on Conspicuous Consumption? - Wiratama, Bayu (Management Analysis Journal, 2022)
The rational behavior of consumers is to get the best product at a low price. This is in accordance with the economic law which states that rational individuals will make as few sacrifices as possible to get more. The act of envy of other people's ownership also affects the behavior of an individual's consumer, this is seen when someone wants to match or want to own an item or facility that is owned by another person. Conspicuous consumption behavior in the current era is growing rapidly because of the internet and social media. Previous research has not explained the relationship between the three variables, namely narcissism , envy and conspicuous consumption. This study also proves that there is no influence of narcissism with excessive buying behavior patterns. Social media has a role in influencing patterns of excessive buying behavior but is unable to moderate the relationship between envy and narcissism. This study was able to conclude that envy arises because individuals see directly or interact with the surrounding environment without going through social media to make excessive buying behavior patterns.